A liberdade é a coisa mais cara da vida (freedom is the most expensive thing in life): artwork by Sara&André, text by Luísa Santos (Universidade Católica Portuguesa) - Santos, Luísa (INYI Journal, 2021)
A short story that came to life through the observation of an artwork by Sara&André, this text is a personal viewpoint on being a mother, an academic and an independent curator, during the current COVID-19 pandemic.